Avaliação dos efeitos do simples nacional sobre o faturamento das micro e pequenas empresas (MPE’s) e arrecadação de ICMS no Estado do Ceará - Carvalho, Afonso Nunes Mendes de (2022)
Micro and Small Enterprises perform a fundamental role in the economy of the State of Ceará, not only for their significant participation in participation in jobs and income generation, given the number of active establishments, but also for their contribution to economic growth and development. Even with this highlight, MSEs have faced great difficulties in surviving the market due to the high tax burden that affects business in Brazil. In view of this, Complementary Law No. 123/2006 was created in Brazil, which established the National Statute of Microenterprises and Small Businesses to provide differentiated treatment and favor to companies classified in these categories. Thus, Simples Nacional (SN) had as its main objective the reduction of the tax burden through a single collection system, including accessory obligations. In that regard, the objective of this research is to evaluate the effects of the SN on the billing of MPEs located in the State of Ceará, as well as the impacts on ICMS collection in the period from 2003 to 2013. The data for this analysis were obtained from the Secretary of Finance of the State of Ceará (SEFAZ), IPECE, and IBGE. The difference-in-difference methos is applied in a panel data structure. The results pointed to an average increase in the revenue of MSEs between 45.9% and 96.4% and an average reduction in ICMS collection between 8.5% and 11.2%.